The Genius is a Male: Stereotypes and Same-Sex Bias in Exam Grading in Economics at Stockholm University - Joakim Jansson; Björn Tyrefors (Research Institute of Industrial Economics (IFN), 2020)
We use the random allocation of graders to different exam questions at Stockholm University to evaluate the existence of same-sex bias in exam correction. We find evidence of same-sex bias before anonymous exams were introduced. Notably, once anonymous grading was in place, the effect disappears. When separating the effects by grader's sex, both groups of graders favor male students, although male graders favor male students to a larger extent than female graders. Again, after anonymous grading was introduced, the effect disappears. There is no evidence of compositional changes across the pre-and post-anonymous grading regimes. In sum, our finding is consistent with theories of stereotyping, e.g., the genius being male.
Keywords: I23; J16; 330; Grading bias; University; Discrimination; Education; Anonymous grading; Same-sex bias